Gestión del conocimiento aplicado: transformación digital y comunidades de prácticas (Tema Central) - Weingärtner Reis, Ingrid (2024)
Knowledge management was developed as an elementary discipline to improve and innovate in organizations. Knowledge, as a base asset, must be treated and amplified so that it can effectively become a competitive differential. The main objective of this study is to understand whether the applied knowledge practices, such as communities of practice as applied in this case, would allow an effective improvement in processes. The methodological design included an interpretive case study based on 100 support processes to academic and university management at the Private Technical University of Loja (UTPL, as per its acronym in Spanish). In order to better use the new implemented technologies, improvements in processes were developed by having teams and groups involved, creating similar structures to those in communities of practice. The results of this study suggest that group organization based in dialogical processes helped create new knowledge that, in turn, caused improvements in the processes of experience of the digital transformation project. A deep narrative interpretation is provided explaining the facts identified during the development of the process improvement activities in a digital transformation project.